PENGEMBANGAN PETUNJUK PRAKTIKUM IPA BERBASIS KULTUR MASYARAKAT PESISIR UNTUK SISWA KELAS VII SMPN 5 SUMENEP - Rasmiati Rasmiati; Lutfiana Fazat Azizah; Herowati Herowati (Faculty of Teaching and Education, University of Wiraraja, 2018)
Problems experienced by students of class VII SMPN 5 Sumenep namely the science practicum instructionsdoes not contain the components clearly and completely. This makes students do not understand the activities practicum performed. The purpose of this research is to know the feasibility of science practicum instructionsbased on coastal community culture, and student and science teacher's response to the practicum instructions. This research is a research and development (Research and Development) by using Sugiyono development model (2018). The subjects of this study were 12 students of class VII SMPN 5 Sumenep selected at random with 3 students on product simulation test and 9 students on the trial of product usage. The results of feasibility of the science practicum instructionsbased on the culture of coastal communities were averaged at 74% with the criteria deserved for the content of the product and 92.7% for the average product display with very deserved criteria. The student's response is obtained on average 100% for product simulation phase and 96,9% on trial of product usage, with the same category that is very good. IPA teachers' responses to the science practicum instructions based on coastal societies culture are included in the excellent category with an average of 100%.